Commemoration of the foundation of the "Internationale Verbindung der sozialdemokratischen Jugendorganisationen", 1907. Voorink in the right background behind the speaker
Commemoration of the foundation of the "Internationale Verbindung der sozialdemokratischen Jugendorganisationen", 1907. Voorink in the right background behind the speaker.